SIMPLE ELASTO-PLASTIC LIMIT ANALYSIS OF PLANE FRAMES SUBJECTED TO COMBINED BENDING MOMENT AND AXIAL FORCE - Wanjala, R. S.; Lwambuka, L.; Branicki, C (Tanzania Journal of Engineering and Technology, 2018)
Abstract